Changing diets: Urbanization and the nutrition transition - Hawkes, Corinna; Harris, Jody; Gillespie, Stuart (International Food Policy Research Institute, 2017)
Diets are changing with rising incomes and urbanization— people are consuming more animal-source foods, sugar, fats and oils, refined grains, and processed foods. This “nutrition transition” is causing increases in overweight and obesity and diet-related diseases such as diabetes and heart disease. Urban residents are making the nutrition transition fastest— but it is occurring in rural areas too. Urban food environments—with supermarkets, food vendors, and restaurants—facilitate access to unhealthy diets, although they can also improve access to nutritious foods for people who can afford them. For the urban poor, the most easily available and affordable diets are often unhealthy.